Body Mass Index as a Predictive Factor of Periodontal Therapy Outcomes. (January 2014) - Suvan, J.; Petrie, A.; Moles, D.R.; Nibali, L.; Patel, K.; Darbar, U.; Donos, N.; Tonetti, M.; D'Aiuto, F.
Body mass index (BMI) and obesity are associated with the prevalence, extent, and severity of periodontitis. This study investigated the predictive role of overweight/obesity on clinical response following non-surgical periodontal therapy in patients with severe periodontitis. Two hundred sixty adults received an intensive course of non-surgical periodontal therapy. Periodontal status at baseline and 2 months was based upon probing pocket depths (PPD), clinical attachment levels (CAL), and whole-mouth gingival bleeding (FMBS) as assessed by two calibrated examiners. Generalized estimating equations (GEE) were used to estimate the impact of BMI and overweight/obesity on periodontal treatment response while controlling for baseline status, age, smoking status (smoker or non-smoker), and full-mouth dental plaque score. BMI (continuous variable) and obesity ( vs . normal weight) were associated with worse mean PPD ( p < .005), percentage of PPD > 4 mm ( p = .01), but not with FMBS ( p > .05) or CAL ( p > .05) at 2 months, independent of age, smoking status, or dental plaque levels. The magnitude of this association was similar to that of smoking, which was also linked to a worse clinical periodontal outcome ( p < .01). BMI and obesity appear to be independent predictors of poor response following non-surgical periodontal therapy.